PENGOLAHAN LIMBAH CAIR INDUSTRI PERCETAKAN UANG KERTAS (UTAS) MENGGUNAKAN PROSES BIOLOGIS ANAEROB - Nugroho, Rudi; Mahmud, Ikbal; Sulasmi, Nurtya (Center for Environmental Technology, 2008)
A research of wastewater treatment technology come from money producing industry was conducted in laboratory scale using 10 lt of Anaerobic Fixed Bed Reactor. The money producing wastewater was treated by mixing with domestic wastewater with various compositions. The wastewater was fed into the bioreactor by draw and fill daily.The results show that the optimum of COD removal is 52,5%, optimum loading is 0, 95 g-COD/l/day and optimum flowrate is 0,5 l/day. The optimum compossition of money producing wastewater towards domestic wastewater is 30%. These optimum conditions can be used as a designed criteria for full scale of anaerobic bioreactor in the money producing industry.Ã‚Â Katakunci : Wastewater, Anaerobic, Fixed Bed Reactor